2006
DOI: 10.1038/sj.emboj.7601159
|View full text |Cite
|
Sign up to set email alerts
|

Musashi regulates the temporal order of mRNA translation during Xenopus oocyte maturation

Abstract: A strict temporal order of maternal mRNA translation is essential for meiotic cell cycle progression in oocytes of the frog Xenopus laevis. The molecular mechanisms controlling the ordered pattern of mRNA translational activation have not been elucidated. We report a novel role for the neural stem cell regulatory protein, Musashi, in controlling the translational activation of the mRNA encoding the Mos proto-oncogene during meiotic cell cycle progression. We demonstrate that Musashi interacts specifically with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
220
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(233 citation statements)
references
References 52 publications
11
220
2
Order By: Relevance
“…However, Mos, the primary MAP kinase activator in oocytes (27)(28)(29), is itself regulated through translational activation by Musashi, suggesting that Musashi must be initially activated by a MAP kinase-independent mechanism (5). Consistent with this hypothesis, it has been previously shown that treatment of oocytes with the MAP kinase signaling inhibitor UO126 does not prevent initial polyadenylation or translation of the Mos mRNA (5,30).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…However, Mos, the primary MAP kinase activator in oocytes (27)(28)(29), is itself regulated through translational activation by Musashi, suggesting that Musashi must be initially activated by a MAP kinase-independent mechanism (5). Consistent with this hypothesis, it has been previously shown that treatment of oocytes with the MAP kinase signaling inhibitor UO126 does not prevent initial polyadenylation or translation of the Mos mRNA (5,30).…”
Section: Resultssupporting
confidence: 68%
“…Translation of Ringo then induces Ringo/CDK activity, leading to the initial activation of Musashi and Musashi-dependent mRNA translation, as reported in this study. Musashi-dependent mRNA translation then mediates subsequent CPEB activation and translation of late class, CPEdependent mRNAs (5,13). The coordinated action of these mRNA translational regulators serves to promote and maintain MPF activity and cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pum2 exerts its effects at least in part by affecting the interaction between the RNA-binding protein DAZL (deleted in azoospermia-like) and the embryonic PABP, but it also may affect polyadenylation [31]. Another translational regulator, Musashi, is implicated in promoting the translation of Mos and Cyclin B5 by binding to the MBE (Musashi-binding element) and acting together with CPE to influence polyadenylation [94,99,100].…”
Section: Developmental Control Of the Cell Cycle Via Translational Rementioning
confidence: 99%